Knockdown of NAA25 Suppresses Breast Cancer Progression by Regulating Apoptosis and Cell Cycle - Xu, Jingkai; Li, Zhi; Zuo, Xianbo; Li, Guozheng; Zhang, Xuejun; Zhang, Bo; Cui, Yong (Frontiers in Oncology, 2022)
NAA25 gene variants were reported as risk factors for type 1 diabetes, rheumatoid arthritis and acute arterial stroke. But it’s unknown whether it could contribute to breast cancer. We identified rs11066150 in lncHSAT164, which contributes to breast cancer, in our earlier genome-wide long non-coding RNA association study on Han Chinese women. However, rs11066150 A/G variant is also located in NAA25 intron. Based on the public database, such as TCGA and Curtis dataset, NAA25 gene is highly expressed in breast cancer tissues and this result has also been proved in our samples and cell lines through RT-qPCR and western blot analysis. To better understand the function of NAA25 in breast cancer, we knocked down the expression of NAA25 in breast cancer cell lines, FACS was used to detect cell apoptosis and cell cycle and colony formation assay was used to detect cell proliferation. We found that NAA25-deficient cells could increase cell apoptosis, delay G2/M phase cell and decrease cell clone formation. RNA sequencing was then applied to analyze the molecular profiles of NAA25‑deficient cells, and compared to the control group, NAA25 knockdown could activate apoptosis-related pathways, reduce the activation of tumor-associated signaling pathways and decrease immune response-associated pathways. Additionally, RT-qPCR was employed to validate these results. Taken together, our results revealed that NAA25 was highly expressed in breast cancer, and NAA25 knockdown might serve as a therapeutic target in breast cancer.